(NH4)3B11PO19F3: a deep-UV nonlinear optical crystal with unique [B5PO10F]∞ layers. Issue 8 (10th June 2022) - Cheng, Bingliang; Li, Zijian; Chu, Yu; Tudi, Abudukadi; Mutailipu, Miriding; Zhang, Fangfang; Yang, Zhihua; Pan, Shilie
Abstract: Deep-ultraviolet (DUV) nonlinear optical (NLO) crystals that can extend the output range of coherent light below 200 nm are pivotal materials for solid-state lasers. To date, KBe2 BO3 F2 (KBBF) is the only usable crystal that can generate DUV coherent light by direct second harmonic generation (SHG), but the layered growth habit and toxic ingredients limit its application. Herein, we report a new fluoroborophosphate, (NH4 )3 B11 PO19 F3 (ABPF), containing four different functional units: [BO3 ], [BO4 ], [BO3 F] and [PO4 ]. ABPF exhibits a KBBF-like structure while eliminating the limitations of KBBF crystal. The unique [B5 PO10 F]∞ layers enhance ABPF's performance; for example, it has a large SHG response (1.2 × KDP) and a sufficient birefringence (0.088 at 1064 nm) that enables the shortest phase-matching wavelength to reach the DUV region. Meanwhile, the introduction of strong B-O-P covalent bonds decreases the layered growth habit. These findings will enrich the structural chemistry of fluoroborophosphate and contribute to the discovery of more excellent DUV NLO crystals. Abstract : This paper reports a new nonlinear optical crystal that has a large second harmonic generation response, a short cutoff edge and a sufficient birefringence for deep-ultraviolet phase matching.